Regional Gravity Model of Greece Based on Satellite, Marine and Terrestrial Data - Dilalos, Spyridon; Alexopoulos, John D. (Pure and Applied Geophysics, 2023)
Greece is a country structured by land, several islands and sea. A regional gravity model of such a country demands the involvement of several types of gravity data in order to cover all its territory. In this paper, we present the development of a regional combined gravity model of Greece and its surrounding area, by integrating terrestrial, marine (shipborne and altimetry-derived gravity data) and satellite data (GOCE and GRACE data). These kinds of data, especially the terrestrial and marine ones, have passed quality and validation control since they were collected from different organizations, which means that they probably have been acquired and processed with different parameters and formulas. Following that, their integration was accomplished with the application of the least-squares collocation (LSC). Therefore, a newly combined regional gravity model of Greece and its surrounding areas has been developed. This gravity model can be valuable for regional geological and geophysical studies of Greece, since it provides homogeneously the distribution of Complete Bouguer anomaly (CBA) all over Greece, with updated gravity data and in good agreement with the initial gravity datasets that have been used.